(613) محاضرات في التخطيط الاقتصادي(عدة أجزاء) Lectures in Economic Planning - محمد مبارك حجير, محمد (معهد التخطيط القومى, 2024)
ملخص تتناول هذه المذكرة التعليمية موضوع التخطيط الاقتصادي باعتباره أحد الأدوات الرئيسية التي تعتمد عليها الدول لتحقيق التنمية الاقتصادية والاجتماعية وتوجيه الموارد المتاحة نحو الاستخدام الأمثل. وتستهدف المحاضرة تقديم إطار نظري ومنهجي لفهم مفهوم التخطيط الاقتصادي، وأهدافه، ومبررات اللجوء إليه في الدول النامية والمتقدمة على السواء. وتبدأ الدراسة بتوضيح العلاقة بين التخطيط والتنمية، مع التركيز على دور التخطيط في معالجة الاختلالات الاقتصادية، وتحقيق التوازن بين الموارد والاحتياجات، ورفع معدلات النمو وتحسين مستويات المعيشة. كما تستعرض المذكرة الأسس الفكرية للتخطيط الاقتصادي ومراحله المختلفة، بدءًا من تحديد الأهداف العامة للتنمية، مرورًا بتقدير الموارد المتاحة، ووضع البرامج والمشروعات اللازمة لتحقيق تلك الأهداف، وانتهاءً بمتابعة التنفيذ والتقييم المستمر للنتائج. وتناقش الدراسة أنواع التخطيط الاقتصادي من حيث المدى الزمني والمجال الجغرافي ومستوى المركزية، موضحةً الفروق بين التخطيط الشامل والتخطيط القطاعي، وبين الخطط قصيرة الأجل ومتوسطة الأجل وطويلة الأجل. كما تبرز أهمية البيانات الإحصائية والمؤشرات الاقتصادية في بناء الخطط التنموية وصياغة السياسات الاقتصادية الرشيدة. وتؤكد المذكرة أن نجاح عملية التخطيط يعتمد على دقة المعلومات، وكفاءة المؤسسات، والتنسيق بين الجهات المختلفة، إضافة إلى القدرة على التكيف مع المتغيرات الاقتصادية والاجتماعية. وتخلص الدراسة إلى أن التخطيط الاقتصادي يمثل عملية علمية منظمة تهدف إلى تحقيق الاستخدام الأمثل للموارد المتاحة، وتسريع وتيرة التنمية، وتحقيق العدالة الاجتماعية والاستقرار الاقتصادي، بما يسهم في رفع كفاءة الأداء الاقتصادي وتحقيق الأهداف القومية للتنمية المستدامة This instructional memorandum examines economic planning as a fundamental instrument through which governments seek to achieve economic and social development and ensure the efficient allocation of available resources. The lecture provides a theoretical and methodological introduction to the concept of economic planning, its objectives, and the rationale for its application in both developing and developed economies. The study begins by explaining the relationship between planning and development, emphasizing the role of planning in addressing economic imbalances, coordinating resources with societal needs, promoting economic growth, and improving living standards. It further discusses the intellectual foundations and major stages of the planning process, including the formulation of development objectives, assessment of available resources, preparation of programs and projects, implementation procedures, and continuous monitoring and evaluation. The memorandum also reviews different forms of economic planning according to time horizon, geographic scope, and degree of centralization, highlighting the distinctions between comprehensive and sectoral planning as well as short-, medium-, and long-term development plans. Particular attention is given to the importance of statistical data and economic indicators in designing development strategies and supporting rational policy formulation. The study stresses that successful planning depends on the availability of reliable information, institutional efficiency, effective coordination among public agencies, and the ability to respond to changing economic and social conditions. It concludes that economic planning is a systematic and scientific process aimed at achieving the optimal utilization of resources, accelerating economic and social development, promoting equity and stability, and enhancing overall economic performance. Consequently, planning serves as an essential framework for guiding national development efforts and achieving long-term sustainable development objectives.